2003
DOI: 10.1095/biolreprod.102.012120
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Undernutrition from Early- to Mid-Gestation Leads to Growth Retardation, Cardiac Ventricular Hypertrophy, and Increased Liver Weight in the Fetal Sheep

Abstract: Early gestation is critical for placentomal growth, differentiation, and vascularization, as well as fetal organogenesis. The fetal origins of adult disease hypothesis proposes that alterations in fetal nutrition and endocrine status result in developmental adaptations that permanently change structure, physiology, and metabolism, thereby predisposing individuals to cardiovascular, metabolic, and endocrine disease in adult life. Multiparous ewes were fed to 50% (nutrient restricted) or 100% (control fed) of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
169
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(186 citation statements)
references
References 46 publications
14
169
1
2
Order By: Relevance
“…Litter-size-dependent IUGR and nutrition insult The observations that blood flow per foetus in twin pregnancies is less than that in singleton pregnancies (Christenson and Prior, 1978), and that concentrations of glucose in the maternal and foetal circulations are lower in twin than in singleton pregnancies (Vonnahme et al, 2003), support the notion that litter-size-dependent IUGR results from the maternal system's inability fully to support growth of multiple conceptuses. However, three lines of evidence suggest that nutrient supply from the dam to the conceptus may not be the sole rate-limiting factor for foetal growth in pregnancies with multiple foetuses, or at least for twin pregnancies.…”
Section: New Paradigm For Litter-size-dependent Iugrmentioning
confidence: 96%
See 2 more Smart Citations
“…Litter-size-dependent IUGR and nutrition insult The observations that blood flow per foetus in twin pregnancies is less than that in singleton pregnancies (Christenson and Prior, 1978), and that concentrations of glucose in the maternal and foetal circulations are lower in twin than in singleton pregnancies (Vonnahme et al, 2003), support the notion that litter-size-dependent IUGR results from the maternal system's inability fully to support growth of multiple conceptuses. However, three lines of evidence suggest that nutrient supply from the dam to the conceptus may not be the sole rate-limiting factor for foetal growth in pregnancies with multiple foetuses, or at least for twin pregnancies.…”
Section: New Paradigm For Litter-size-dependent Iugrmentioning
confidence: 96%
“…Increases in total foetal body mass in pregnancies with multiple foetuses raise the demand for glucose. Accordingly, plasma concentrations of glucose in the foetus and ewe in the case of twin pregnancies are 20% and 30% less, respectively, than for singleton pregnancies during late gestation (Edwards and McMillen, 2002;Vonnahme et al, 2003). The decline in plasma glucose concentration may be associated with changes in glucosetransporter abundance or activity; however, this has never been investigated in multiple pregnancies.…”
Section: Cardiovascular and Uterine Blood Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that maternal undernutrition from early-to mid-gestation leads to cardiac hypertrophy in fetal sheep. 8 Further study with GA-matched infants would be required to differentiate differences in cardiac and thoracic growth.…”
Section: Discussionmentioning
confidence: 99%
“…These include the intrauterine changes in cardiovascular mechanics that redistribute blood flow from body to brain in the presence of fetal growth retardation. [1][2][3][4][5][6] In later life, left ventricular hypertrophy is a strong predictor of stroke, heart failure and coronary artery disease. 7 Growth in infancy and childhood also appear to modulate the risk of hypertension, stroke and coronary artery disease, and thus might relate to left ventricular hypertrophy.…”
Section: Introductionmentioning
confidence: 99%